PENGELOLAAN TANAMAN SAGU DI SULAWESI TENGGARA - Suharno Suharno (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2010)
Sago plan tree is the main of food raw in Southeast Sulawesi. The sago powder could made the fod like sinonggi and other snack. The sago palm wide areas in Southeast Sulawesi is 5.083 hectares, most growth in several district in Southast Sulawesi especially in costal region. The sago palm tree is the several utilitized plant. Most of several part of tee has the economics value. Therefore the sago palm tree nmanagemnet is still an exploitations for economic objectives not conservation yet. The sago process has done in long time ago. There are two ways to processing the sago powder, one method do by traditional and other by machine, but most people change to the machines process now. The paper described the management of sago palm management and also economic benefit of sago palm tre in Southeast Sulawesi focused on powder production in Konawe and Kendari district. The result analysis of sago powder processing indicated that farmer found revenue Rp 568.750 per tree on R/C Ratio 2,71.